“Protecting the Dao and transmitting the classics”: the new religion to save the world and the Confucian dimension of spirit-writing in Republican China - Schumann, Matthias (Communicating with the Gods, 2024)
Abstract In this chapter, Matthias Schumann explores the role of Confucian texts and Confucianism more generally within redemptive societies by examining the case of the Jiushi xinjiao 救世新教 (New Religion to Save the World). He shows how members of the society, many of whom were trained under the traditional education system, strove to come to terms with the complicated Confucian legacy at a time when many reformers considered it obsolete. From the mid-1920s onward, a number of members, most prominently the politician Lu Zongyu 陸宗輿 (1876-1941), began to transmit commentaries on the Confucian classics through spirit-writing. Through the production of these texts, which included commentaries on the Daxue 大學 (Great learning) and the Zhongyong 中庸 (Doctrine of the mean), they integrated the Confucian classics into their own religious program of self-cultivation and moral reform, providing an innovative reading by stressing the role of the deities as the agents of retribution. Thereby, they claimed to have finally restored the true interpretation of these important texts and emphasized the classics’ continued cultural value for the Chinese nation.